Pengaruh Pendekatan Matematika Realistik Indonesia Menggunakan Media Biji Kolang-Kaling Berwarna Terhadap Hasil Belajar Matematika Materi Bilangan Bulat Kelas V SDN 12 Simpangkatis - Ayu Chayati; Sri Sugiyarti; Yudi Yunika Putra (Jurnal Inovasi Matematika, 2019)
The purpose of this research is to determine the effect of Indonesian Realistic Mathematical approach by using the colorful of sugar palm seeds to students’ mathematics learning outcomes of integers material for the fifth grade at used is SD Negeri 12 Simpangkatis.The method in this research is a quantitative research method with the type of quatitave research in experimental form with the design of one group pretest-posttest design. This research was conducted in class V at SD Negeri 12 Simpangkatis, Bangka Tengah District, this research was conducted in the first semester of the Academic year 2018/2019. The population in this research were all fifth grade students at SD Negeri 12 Simpangkatis Academic Year 2018/2019 which consisted of 27 students. The sample in this research was the fifth grade students of SD Negeri 12 Simpangkatis with a total of 27 students, who were taken using Saturation Sampling techniquesThe results of this research indicate that the Indonesian Realistic Mathematical approach by using the colorful of sugar palm seeds to students’ mathematics learning outcomes of integers material for the fifth grade at SD Negeri 12 Simpangkatis. This is based on increased posttest results compared to the results of the pretest. In addition, the results of the hypothesis test obtained by the value of the results is tcount: 12.444 and ttabel: 1.703 based on criteria, tcount<ttabel then Ha is accepted tcount<ttabel Ho is rejected. The result is that there is an effect of Indonesian Realistic Mathematical approach by using the colorful of sugar palm seeds to the students’ mathematics learning outcomes in integers material for the fifth grade at SD Negeri 12 Simpangkatis.